Akurasi Dimensi Komponen Multi-material Hasil Manufaktur Digital Light Processing (DLP) 3D Printing - Budi , Arifvianto; Yusron, Wijanarko Zidan; Muslim , Mahardika (Indonesian Journal Publisher, 2024)
Workpieces resulting from 3D printing manufacturing which were initially only for rapid prototyping purposes, are now used for final products. In its development, a method is needed that can accommodate the creation of multi-material structures because there are complex structures that require hard materials and elastic materials in one part at once. Multi-material manufacturing with a laminate structure in DLP 3D printing can be done by changing the resin material periodically as needed. One important aspect in multi-material 3D printing manufacturing is dimensional accuracy. In this research, the accuracy of multi-material specimen layer thickness from DLP 3D printer manufacturing was studied. The specimens were manufactured with a uniform CAD design, but with varying numbers of material layer pairs. The thickness of each layer of the specimen is measured. From the measurement results, it is known that there is an error in the thickness of each specimen due to the bottom layer phenomenon and the influence of the penetration range of UV light in the DLP 3D printing technique due to differences in the color density of the resin material and the concentration of the photoinitiator.